Bhutan’s Labor Market : Toward Gainful Quality Employment for All - World Bank Group; Ministry of Labor and Human Resources, Royal Government of Bhutan (Washington, DC: World Bank, 2016)
The Royal Government of Bhutan (RGoB) places great emphasis on the creation of a sufficient number of high-quality jobs to achieve full employment. This report aims to provide robust evidence to inform the RGoB’s policy-making with regard to critical labor market challenges, underlying causes and potential solutions. Building on a conceptual framework introduced in the World Bank’s World Development Report 2013: Jobs, the analysis takes into account policy fundamentals that are essential for both growth and job creation, labor market policies that can help ensure that growth translates into employment opportunities and a list of policy priority areas where jobs might do the most for development given Bhutan’s specific country context. The report relies primarily on two data sources that provide recent robust and complementary information on labor supply and demand in Bhutan: First, the Bhutan Labor Force Survey (BLFS) 2014, a representative labor force survey with a newly expanded questionnaire that was implemented by the MoLHR with support from the World Bank. Second, the Bhutan Enterprise Survey (BES) 2015, a survey of firms conducted by the World Bank that improved the understanding of the conditions, experiences and perspectives of Bhutan’s nonfarm private firms. The report also uses evidence from previous studies, legal documents, and discussions with experts and stakeholders from Bhutan and beyond.